Oxidative dehydrogenation of ethylbenzene over vanadia-alumina catalysts in the presence of nitrous oxide: structure-activity relationship - Shiju, N. R.; Anilkumar, Mettu; Mirajkar, Subhash P.; Gopinath, Chinnakonda S.; Rao, B. S.; Satyanarayana, C. V. (Journal of Catalysis, 2005)
A series of vanadia-alumina catalysts with different vanadia contents were prepared by a wet impregnation method. The influence of the local structure of vanadia in these catalysts on the oxidative dehydrogenation of ethylbenzene with nitrous oxide was investigated. The use of N2O as a co-feed remarkably enhanced the styrene yield compared with the use of N-2. Characterization of these vanadia catalysts by XRD, FTIR, UV-vis, TPR, XPS, and V-51 NMR techniques suggests that the nature of the VOx species depends on the vanadia loading: the predominant species are monomeric vanadia at lower loadings, two-dimensional polyvanadates at intermediate loadings, and bulk-like V2O5 and AlVO4 at higher loadings. The rate of oxidative dehydrogenation (ODH) of ethylbenzene per vanadium atom increases with vanadia loading and reaches a maximum at 10 wt%, the loading at which the surface predominantly contains polyvanadate species. The observed variation in the selectivity of products with vanadium loading indicates that the monomeric V5+ species favors dehydrogenation, whereas bulk-like V2O5 preferentially participates in the dealkylation of ethylbenzene. The vanadium species remains at a higher oxidation state in the presence of N2O, leading to a higher styrene yield. than in a N-2 atmosphere. The ODH turnover rates increased with decreasing energy of the absorption edge in the UV-vis spectrum, at low VOx coverages of less than one monolayer on the Al2O3 surface. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: absorption edge energy; Alumina; ethylbenzene; Nitrous oxide; oxidative dehydrogenation; polyvanadates; styrene; vanadia

Catalyst deactivation and regeneration - Satyanarayana, C. V.; Srikant, D.; Gurav, H. R. (Industrial catalytic processes for fine and specialty chemicals, 2016)
Catalysis plays a vital role in the manufacture of fuels, industrial chemicals, fine chemicals, and specialty chemicals. A catalyst is not only expected to be highly active, it should be stable for long hours on stream and should be recyclable, if required. However, in reality, all the catalysts have finite life. Hence, a most important goal of any catalyst development is to get a catalyst that is highly active for long periods without needing any regeneration. This chapter addresses various causes of catalyst deactivation with reference to different catalyst systems. It discusses various forms coke (carbon) forms on catalysts and the side reactions that drive their formation. The role of support on carbon formation as well as how carbon can be limited using bimetallic catalysts is discussed. Various mechanisms responsible for sintering of metals have been discussed while suggesting means to suppress the same. This chapter also discusses loss of catalyst activity due to strong chemisorption of impurities or byproducts. Typical poisons to different catalysts are listed. The effect of various poisons and how they can influence the course of a catalytic reaction are described. A catalyst may also lose its activity due to mechanical failures such as (i) crushing of catalyst pellets or granules, (ii) breakup of catalyst pellets followed by its attrition, and (iii) erosion of catalyst particles or monolith wash coats. Various solutions to prevent or delay catalyst deactivation as well as various catalyst regeneration methods are summarized.